In situ mechanical quenching of nanoscale silica spheres in the transmission electron microscope. (August 2016) - Mačković, M.; Niekiel, F.; Wondraczek, L.; Bitzek, E.; Spiecker, E.
Abstract: A novel approach for in situ mechanical quenching experiments of nanoscale silica spheres inside the transmission electron microscope is presented. Electron irradiation is used to mimic temperature by mediating plastic flow. Quenching under load is achieved by switching-off the electron beam. This is employed in different loading scenarios. Complementary finite element method simulations underline a change of Young's modulus, which strongly depends on the interplay of electron irradiation and mechanical load. We attribute the reduction in Young's modulus to compression-induced structural anisotropy which is frozen-in by rapid quenching and propose a model on how structural anisotropy develops in nanoscale silica. Graphical abstract: